Model Epidemi SIR (Susceptible-Infected-Removed) pada Penyebaran Penyakit HIV/AIDS di Provinsi Sumatera Utara - Miranda Olivia; Fitra Muliani; Ulya Nabilla (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2026)
Human Immunodeficiency Virus (HIV) is a virus that attacks the immune system, especially the white blood cells. HIV progresses to Acquired Immunodeficiency Syndrome (AIDS) if not treated effectively. Generally, people with this disease have several symptoms such as fever, chills, rash, muscle pain, sore throat, and fatigue. HIV/AIDS can cause serious complications, such as heart disease, nervous disorders, and problems with the digestive system, even death. North Sumatra ranks fifth nationally for HIV/AIDS sufferers. Mathematical modeling in the spread of HIV/AIDS aims to analyze the equilibrium point, analyze the rate of spread of HIV/AIDS, and project the number of cases in the future. This model involves three variables, namely Susceptible (S), Infected (I), and Recovered (R). The research data were obtained from Dinas Kesehatan Sumatera Utara dan Badan Pusat Statistik (BPS) Provinsi Sumatera Utara. The results showed that the equilibrium point is stable. The transmission rate is 0.000129/day. By using Next Generation Matrix (NGM), the basic reproduction number ( ) is 28.981. It means that the disease will become endemic over a long period of time.